Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/molecules23102486
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Toxicity Studies of Cortex Dictamni Extracts in Mice and Its Potential Hepatotoxicity Mechanisms in Vitro

Abstract: Cortex Dictamni is a commonly-used traditional Chinese herbal medicine for the treatment of skin inflammation, tinea, and eczema. Recently, some studies reported that Cortex Dictamni might induce liver injury, suggesting more attention to its safety. The current study was designed to investigate subchronic toxicity of Cortex Dictamni aqueous extract (CDAE) and ethanol extract (CDEE) in mice and the potential hepatotoxicity mechanisms in vitro. Firstly, CDAE or CDEE groups were administrated with varying dosage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…It has been prescribed for the treatment of rheumatism, coronary atherosclerosis, jaundice and skin disorders (Chang, Lan, Yang, & Heinrich, 2016; Lv et al, 2015). However, the safety of this herb medicine has been questioned because some reports indicated that the oral administration of Dictamni cortex resulted in severe liver injury (Efferth et al, 2017; Fan et al, 2018; Wang et al, 2014; Wang, Xu, & Wang, 2007). Obacunone, one of the triterpenoids from Dictamni cortex, was the major bioactive constituent of this herb (Fan et al, 2018; Nam et al, 2005), which has been demonstrated to have anti‐cancer activity (Chidambara Murthy, Jayaprakasha, & Patil, 2011; Murthy, Jayaprakasha, & Patil, 2015; Tanaka et al, 2000, 2001; Xie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been prescribed for the treatment of rheumatism, coronary atherosclerosis, jaundice and skin disorders (Chang, Lan, Yang, & Heinrich, 2016; Lv et al, 2015). However, the safety of this herb medicine has been questioned because some reports indicated that the oral administration of Dictamni cortex resulted in severe liver injury (Efferth et al, 2017; Fan et al, 2018; Wang et al, 2014; Wang, Xu, & Wang, 2007). Obacunone, one of the triterpenoids from Dictamni cortex, was the major bioactive constituent of this herb (Fan et al, 2018; Nam et al, 2005), which has been demonstrated to have anti‐cancer activity (Chidambara Murthy, Jayaprakasha, & Patil, 2011; Murthy, Jayaprakasha, & Patil, 2015; Tanaka et al, 2000, 2001; Xie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Obacunone, one of the triterpenoids from Dictamni cortex, was the major bioactive constituent of this herb (Fan et al, 2018; Nam et al, 2005), which has been demonstrated to have anti‐cancer activity (Chidambara Murthy, Jayaprakasha, & Patil, 2011; Murthy, Jayaprakasha, & Patil, 2015; Tanaka et al, 2000, 2001; Xie et al, 2019). However, obacunone was also suggested to be one of the potentially hepatotoxic ingredients (Fan et al, 2018; Lang, Zhang, Wang, & Zhou, 2020). Lang et al indicated that a single oral dose of 50 mg/kg of obacunone resulted in the increase in alanine aminotransferase and aspartate aminotransferase in mice serum and cytochrome P3A4‐mediated bioactivation would be involved in obacunone‐caused liver injury (Lang, Zhang, Wang, & Zhou, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic hepatotoxicity refers to the direct toxic stress leading to hepatic cells death associated with a predictable liver injury that can be reproduced in animal models in a dose-dependent manner. Water and ethanol extracts of DC have potential hepatotoxicity in sub-chronic toxicity studies, with the alcohol extraction process increasing the toxicity level ( Fan et al, 2018 ). In our in vitro and in vivo study, dictamnine was a possible toxic component by high content analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary findings in our study revealed that aqueous and ethanol extracts of DC have potential hepatotoxicity. The hepatotoxic component in DC has been confirmed as dictamnine by liquid chromatography with tandem mass spectrometry (LC-MS/MS) ( Fan et al, 2018 ). However, the precise pathogenesis mechanism of dictamnine-induced hepatotoxicity remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Dictamni cortex, a widely used herbal medicine in China, was reported to cause liver injury [3][4][5]. However, the mechanism behind this has not been adequately investigated.…”
Section: Discussionmentioning
confidence: 99%